Urban gardening and the struggle for social and spatial justice - Certomà, Chiara; Noori, Susan; Sondermann, Martin (Manchester University Press, 2019)
In this book urban gardening is critically discussed as socio-political action which addresses spatial justice as well as social cohesion, inclusiveness, social innovations and equity in cities.